2012
DOI: 10.1007/978-3-642-34191-5_7
|View full text |Cite
|
Sign up to set email alerts
|

The Chromatic Number of the Convex Segment Disjointness Graph

Abstract: Let P be a set of n ≥ 4 points in general position in the plane. Consider all the closed straight line segments with both endpoints in P . Suppose that these segments are colored with the rule that disjoint segments receive different colors. In this paper we show that if P is the point configuration known as the double chain, with k points in the upper convex chain and l ≥ k points in the lower convex chain, then k + l − 2l + 1 4 − 1 2 colors are needed and that this number is sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Let χ(D n ) denote the chromatic number of D n . A lower bound on this value was obtained by Fabila-Monroy and Wood in [11], while an upper bound was obtained by Dujmović and Wood in [8]. Both bounds combine into the following theorem:…”
Section: Blocking the 4-holes Of Convex Point Setsmentioning
confidence: 93%
See 1 more Smart Citation
“…Let χ(D n ) denote the chromatic number of D n . A lower bound on this value was obtained by Fabila-Monroy and Wood in [11], while an upper bound was obtained by Dujmović and Wood in [8]. Both bounds combine into the following theorem:…”
Section: Blocking the 4-holes Of Convex Point Setsmentioning
confidence: 93%
“…Then D n has n 2 − n vertices. It is easy to see from the proof of Theorem 2.2 in [11], that the chromatic number of D n satisfies:…”
Section: Blocking the 4-holes Of Convex Point Setsmentioning
confidence: 99%
“…The graph on the right is the edge disjointness graph D(P ) corresponding to P . value of χ(D(P )) is known only for two particular cases: when P is in convex position Fabila-Monroy and Wood (2011); Jonsson (2011), and when P is the double chain Fabila-Monroy et al (2020). In 2017 Pach, Tardos, and Tóth Pach et al (2017) studied the chromatic number and the clique number of D(P ) in the more general setting of R d for d ≥ 2, i.e., when P is a subset of R d .…”
Section: Introductionmentioning
confidence: 99%
“…The problem of determining the exact value of χ(D(P)) remains open in general. On the other hand, there are only two families of point sets for which the exact value of χ(D(P)) is known: when P is in convex position [11,12], and when P is the double chain [13]. The connectivity κ(D(P)) of D(P) was studied by Leaños, Ndjatchi, and Ríos-Castro in [14], where it was shown that κ(D(P)) ≥…”
Section: Introductionmentioning
confidence: 99%